Le corps sujet des contraires et la dynamique prudente des dispositiones corporis - Laurent Bove (Astérion)
The dynamic complexity of the dispositions (or arrangements) of a body [dispositiones corporis] is cleared up from examining the question of contraries (E3p5 and E5ax1). The reasoning behind this is the same as that behind the causality of each thing’s effort to persevere in and through itself [in suo esse] (Spinoza wrote, « dispositio seu conatus »). « Prudence », which implies the principles of union and resistance, is studied under the theme of habituation and according to bodies’ self-organizing principle.